Juvenile Delinquency and Delinquency, their Prevention - Saidovna, Turdieva Nigora; Bobomurodovna, Karrieva Anora (European Journal of Life Safety and Stability (2660-9630), 2022)
The article deals with the current problem of juvenile delinquency. The problems of finding and establishing a humane approach to solving the issues of preventing and suppressing juvenile delinquency are considered.